COMBINED METHODS OF TATTOOS AND PERMANENT MAKEUP REMOVAL: LASER AND ADJUVANT TECHNOLOGIES - Mikalai Varabyou (Modern American Journals, 2025)
This paper analyzes modern methods of laser tattoo and permanent makeup removal, highlights the advantages of combined techniques, and discusses their practical application, as well as the risks and limitations. The focus is on individualizing the approach, selecting laser parameters, and adjuvant therapy strategies to maximize effectiveness and minimize complications.
Keywords: Laser tattoo removal, permanent makeup, Q- Switched laser, picosecond laser, fractional ablation, combination therapy, pigment complications.